ROLE OF DERMATOGLYPHICS IN EARLY DETECTION OF BRONCHIAL ASTHMA AMONG SOUTH INDIAN POPULATION (Journal of Forensic Medicine & Toxicology, 2022)
Background: Dermatoglyphics is a branch of genetics concerned with the analysis of patterns of integumentary fine ridges of fingers, palms and soles .The development of dermatoglyphic patterns is under genetic control and in general the genetics are multifactorial and highly complex. Abnormal dermatoglyphic patterns have been observed in several non-chromosomal genetic disorders and other diseases whose etiology may be influenced, directly or indirectly, by genetic inheritance. Hence if a meaningful association can be established between dermatoglyphic patterns and bronchial asthma it may be of use in screening the general populations at a very low cost.
Keywords: Dermatoglyphics; Bronchial Asthma; Early Detectio